Thrombotic thrombocytopenic purpura - Sadler, J. Evan (Henry Stewart Talks, 2007)
Idiopathic thrombotic thrombocytopenic purpura, Diagnosis, Treatment, Prognosis, Recent discoveries in pathophysiology, ADAMTS13 metalloprotease, Clinical studies in familial and autoimmune TTP, Frontiers of clinical research
Reviewed at 2015/08/28